The Coalition Against Typhoid: Mobilizing a Community for a Global Fight. (7th March 2019) - Lindsay, Sarah; Gellin, Bruce; Lee, Alice; Garrett, Denise
Abstract: Typhoid became a low priority on the global public health agenda when it was largely eliminated from developed countries in the 1940s. However, communities in South Asia and sub-Saharan Africa continue to bear the brunt of the disease burden. One strategy to increase attention and coordinate action is the creation of a coalition to act as a steward for typhoid. The Coalition against Typhoid (CaT) was created in 2010 with the mission of preventing typhoid among vulnerable populations through research, education, and advocacy. CaT successfully raised the profile of typhoid through convening the community with a biennial international conference that has experienced growing participation, disseminating data and news through a website and newsletter with increasing readership, and advocating through social media and a blog reaching a diverse audience. In 2017, CaT joined forces with the Typhoid Vaccine Acceleration Consortium to "Take on Typhoid, " combining advocacy and communications efforts to mobilize researchers, clinicians, and decision makers at the global, regional, and local levels to introduce the new typhoid conjugate vaccine. As a result, the knowledge base, political will, and momentum are increasingly in place to implement prevention and control interventions including the typhoid conjugate vaccine in the poor communities that have historically been left behind.